ANALISIS DAYA SAING DAN FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR CPO INDONESIA KE CHINA, MALAYSIA, DAN SINGAPURA DALAM SKEMA ASEAN-CHINA FREE TRADE AGREEMENT - Widyastutik Widyastutik; Ahmad Zaenal Ashiqin (Jurnal Manajemen & Agribisnis, 2011)
The Objective of this research is to analyze the competitiveness and the factors that influence Indonesia CPO export to China, Malaysia, and Singapore in the ACFTA. Revealed Comparative Advantage was used to analyze competitiveness in China, Malaysia, and Singapore. Panel data regression method with fixed effect (cross section weight) was used to analyze export supply model as an impact of ACFTA. The results shows that all dependent variables (domestic production of CPO), international price of CPO, price domestic of CPO, price of soybean oil, price of gasoline, exchange rate, lag of export, and dummy of ACFTA have the significant influence on CPO export to China, Malaysia, and Singapore.   Keywords: CPO, ASEAN-China, Revealed Comparative Advantage (RCA)